Resepsi Mahasiswa Sastra Jerman terhadap Nilai Moral yang Terdapat dalam Film Almanya: Willkommen In Deutschland - Taqilla, Firstyera; Afifah, Lilis (Universitas Negeri Malang, 2024)
Nowadays, film is one of educational media that brings valuable messages to their viewers. This research aimed to elaborate receptions of German Department students’ class of 2017 and 2018 about moral value figured on Almanya: Willkommen in Deutschland film. There were three purposes of this research. Firstly, was to categorize the German Department students’ reception and reaction to the film which were divided into several meanings and readings, secondly was to identify moral value in film, and the last one was to find out the positive values figured on Almanya: Willkommen in Deutschland film. This research used qualitative method with descriptive approaches. The data were taken from semi structured interview with ten students of German Department. The gathered data were then analyzed qualitatively. The results show that German Department students have good receptions and reactions about this film and each of them being placed either dominant-hegemonic reading, negotiable reading, or oppositional reading according to their point of view. In particular, the moral values figured on this film are honesty, bravery, hard work, trustworthy, togetherness, tolerance, wisdom, and religious. Lastly, German Department students believe that this film is suitable for educational purposes since it has plenty of positive values.